An Analytical Study to Assess the Effect of Kalusha Prasadan Dravya in Purification of Water W.S. R. to Bisgranthi - Dayal, Shambhu; Samagandi, Kashinath (International Research Journal of Ayurveda & Yoga, 2020)
The whole world is covered with the water and nothing is possible without the water. Absence of clean water and sanitation are major risk for ill health. Water is said to be polluted or contaminated when it does not fill the safe water criteria that is free from physical, chemical and biological impurities. Ayurveda described the methods to identify the impure water and suggests many water purification techniques. Ayurveda especially Sushruta Samhita emphasize the various methods of purification of water on the basis of the amount of contamination. So, here an attempt made to evaluate the effect of Bisgranthi among the Sapta Kalusha Prasadana Dravya in yielding the potable water Material and method: The Sample of untreated water was collected from the Bisalpur reservoir in 05 liter of sterilized water cane and the Bisgranthi was purchased from the shop Result: There are significant changes seen in physical, chemical and biological parameters after the treatment of raw water with Bisgranthi. Discussion & Conclusion: It is concluded that the Kalusha Prasadan Dravya specially Bisgranthi mainly worked on physical and Biological parameters of water.